2010
DOI: 10.1002/uog.8801
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors presenting as gynecological masses: usefulness of multidetector computed tomography

Abstract: Large extraluminal gastrointestinal tumors (GISTs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…Nongynecologic leiomyomas of the pelvis are rare and may involve the bladder (endovesically, intramurally, and extravesically, with frequency rates of 63%, 7%, and 30%, respectively), retroperitoneum, or distal gastrointestinal tract. [2][3][4][5][6] Interestingly, gastrointestinal hemorrhage (absent in our case) has been reported with cases of both endoluminal and extraluminal rectal leiomyomas. 4,5 Classically, a decrease in stool caliber has been described in association with colorectal cancer, yet this finding has recently been challenged.…”
supporting
confidence: 53%
“…Nongynecologic leiomyomas of the pelvis are rare and may involve the bladder (endovesically, intramurally, and extravesically, with frequency rates of 63%, 7%, and 30%, respectively), retroperitoneum, or distal gastrointestinal tract. [2][3][4][5][6] Interestingly, gastrointestinal hemorrhage (absent in our case) has been reported with cases of both endoluminal and extraluminal rectal leiomyomas. 4,5 Classically, a decrease in stool caliber has been described in association with colorectal cancer, yet this finding has recently been challenged.…”
supporting
confidence: 53%
“…Literature has described signs that help localize the epicenter: The presence of a pedicle connecting the mass to the organ of origin is "pedicle sign," as seen in this case [2]. A few other signs are the "beak sign," a sharp angle between the ovary and the mass forms a beak shape at the edge of the ovary; the "phantom organ sign," nonvisualization of an organ in the context of no appropriate surgical history; the embedded organ sign, the organ of origin appears embedded in the mass.…”
Section: Discussionmentioning
confidence: 86%
“…(SMA). The vasculature of G-GISTs has been reported in two cases (7). Cai et al (8) reported on the vasculature of D-GISTs, especially the importance of the supply arteries and drainage veins in differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%